Effects of Barium‐Copper‐Cobalt oxide composites supported on reduced graphene oxide in the thermolysis of ammonium perchlorate and 3‐nitro‐1, 2, 4‐triazol‐5‐one. Issue 9 (2nd March 2023) - Dave, Pragnesh N.; Sirach, Ruksana
Abstract: Synthesis method of nanocrystalline Barium‐Copper‐Cobalt oxide (BCC) and its composite with reduced graphene oxide (rGO) was provided. The size of nanocrystalline (∼13 nm) materials (BCC and BCC/rGO) was confirmed using powder X‐ray diffraction patterns. The effect of rGO, BCC, and BCC/rGO on the thermal decomposition of 3‐Nitro‐1, 2, 4‐triazol‐5‐one (NTO) and ammonium perchlorate (AP) was investigated using simultaneous thermal analysis. Non‐isothermal isoconversion method was used to calculate the activation energy of AP and NTO with and without rGO, BCC, and BCC/rGO. The thermal analysis suggests that in the presence of BCC and BCC/rGO, the thermal decomposition exotherm of NTO was lowered to ∼259, and ∼228 °C, respectively, and that of AP was lowered to 355, and 345 °C, respectively. BCC and BCC/rGO exhibit very good catalytic activity for the thermal decomposition of NTO by lowering NTO's activation energy barrier by ∼179 and 261 kJ mol −1, respectively. The activation energy calculations for low thermal decomposition and high thermal decomposition of AP (∼95 kJ mol −1 average) do not provide conclusive evidence to confirm the catalytic influence of BCC and BCC/rGO. The composition NTO+BCC has a lower activation energy barrier (∼121 kJ mol −1 ) than pure NTO which makes the thermal decomposition of NTO+BCC more favorable than pure NTO making its application in insensitive munitions more favorable. AP+BCC decomposes within a short temperature range and hence, it can be used in solid rocket propellants requiring faster decomposition of AP in place of pure AP. Abstract : Thermal decomposition of ammonium perchlorate and 3‐Nitro‐1, 2, 4‐triazol‐5‐one in the presence of Barium‐Copper‐Cobalt oxide catalyst, reduced graphene oxide and their composite can decrease the thermal decomposition temperature and facilitate the decomposition of ammonium perchlorate and 3‐Nitro‐1, 2, 4‐triazol‐5‐one for high energetic applications.